Sportas ir politika: vokiečių sportinė veikla Klaipėdos krašte 1923-1939 metais - Jakubavičienė, Ingrida (Lietuvos istorijos studijos, 2006)
Since 1920 national European countries made their efforts to support their national policy and it caused problems among national minorities and they started actions in order to keep their national identity. In Klaipėda region there were over 65 thousand Germans. There they had a number of sport clubs and cultural, political, religious organizations. In 1923 Klaipėda region was appended to Lithuania but Germans never abandoned their revanchist sentiments to return the region to Germany. Since 1933 as Hitler came into power in Germany, Germans in Klaipėda started Nazi policy. The leaders of sports clubs were members of Nazi organizations and they started military training in the clubs, some sportsmen became shock troops. The German sport organizations showed a clear political support for National Socialism and Hitler’s policy in Germany. In 1934 Nazi organizations in Klaipėda were closed and their leaders were imprisoned for illegal work, so the Germans decided to continue Nazi policy in legal organizations, such as sport clubs. German sport clubs in Klaipėda had a big number of members (in 1931 - 28 clubs with 2199 members, in 1936 - 52 clubs with 2907 members, in 1938 - 75 clubs and more than 3000 members), a lot of various sport clubs, good material basis and financial support from Germany. German sport clubs wanted to stay apart from Lithuanian teams. German sportsmen competed only among their clubs or with clubs in Germany. The leaders of German sport organizations even refused to send German sportsmen to an international sport tournament to represent Lithuania. Such a behavior caused some conflicts between German sport clubs and Lithuanian authorities. Every effort of Lithuanian Palace of Physical Culture (Kūno kultūros rūmai) to make German clubs observe Lithuanian laws was unsuccessful. Every time the resistance of German sport clubs grew stronger. At the end of the conflict with Lithuanian authorities in 1938 the German leading sport organization „Sportbund" proclaimed its isolation from Lithuanian authorities. In general German sport clubs in Klaipėda region since 1930s ignored Lithuanian sport clubs, refused to play and compete with Jewish sport clubs, and demonstrated chauvinism. In Lithuania there were about 30 thousand Germans, they had only two sport clubs: „K.S.K. Kultus" in Kaunas and „Sportverein" in Kybartai. Both were loyal to Lithuanian authorities and participated in Lithuanian competitions. These clubs were quite in a long distance from Klaipėda region, they had a small number of members and received neither political nor financial support from Germany.